Perception of construction company on quality assessment system in Johor Bahru - Nurul Nadia, Hamidon (2017)
There are many factors that may contribute to the success of producing quality product for construction project in Malaysia. One of the factors that consider as the contributor is by using legitimate monitoring checklist as assessment. In Malaysia, Quality Assessment System in Construction (QLASSIC) had been implemented since year 2007. According to building product, quality is an important matter that always concerned by house buyers, investor, contractor and developer. All the qualities of building products depend on how the contractors or developers build it and how they control quality management. Every buyer hopes the construction that they purchase achieved the standard character. Hence, this study focused on the perception of Construction Company on Quality Assessment System in Construction. The aim of this research is to study the perception of Construction Company on Quality Assessment System in Johor Bahru.The objectives of the study are to identify the perception using Quality Assessment System among construction companies in JB, to identify the set back of construction companies in Quality Assessment System implementing, and to propose suitable measures to encourage the use of Quality Assessment System in the construction industry. The questionnaire had been used as the main research methodology in order to obtain those relevant data. Survey form that consists of three sections is prepared for the participants. The first section is the demographic profile of the respondent, such as profession, year of experience and related experience. This information can help to find out the level of implementation in the construction industry. Second part of the survey form is the closed ended question which includes leading questions, important questions, selection questions and Likert Scale questions. At the end of section 1 and section 2, section 3 consists of one open ended question where the respondents are allowed to add to their own opinion on Quality Assessment System in Malaysia. There were about 100 copies of questionnaires were distributed to the targeted respondents consisted of main contractors, subcontractor, consultant and personal that involved in the construction field. By the cut off date, the researcher managed to collect back 50 useable questionnaires from the respondents. In summary, the questionnaire highlighted three main aspects that important in this research. Based on respondents’ feedback, the main issues are on their knowledge about this system.